An Empirical Study of the Impact of Free Cash Flow on Overinvestment: Based on the data of China's listed real estate companies from 2010 to 2018 - Shen, Wenqing (2020)
Modern corporate structures have led to a gradual separation of ownership and control of the firm, which has led to an increase in agency problems. Free cash flow and over-investment caused by agency problems have begun to receive attention from researchers in recent years. Based on the 2010-2018 data of listed real estate companies in China, this research adopts a quantitative research approach to verify the link between free cash flow and over-investment and finds a positive correlation between free cash flow and over-investment. Firms with more free cash flow face more severe overinvestment. However, overinvestment due to free cash flow is also influenced by several factors, such as managerial overconfidence, type of ownership, equity concentration, institutional ownership, and managerial ownership. A discussion of these factors reveals that state-owned enterprise (SOEs) are more subject to political control and that increased equity concentration is not an effective deterrent to free cash flow over-investment. The virtual absence of major owners in SOEs leads to multiple levels of principal-agent relationships and weak supervision of regulators. Overinvestment in non-state holding companies is more sensitive to free cash flow than in state-owned companies because private firms are freer and thus overinvestment is more severe. In the case of non-state-owned holding companies, equity concentration can unify the interests of the majority shareholders and the company, thus providing an incentive for the majority shareholders to take on the responsibility of supervising management. Also, the appropriate use of institutional and managerial shareholdings can, for all enterprises, discourage over-investment to some extent.